PENGUATAN KARAKTER GOTONG ROYONG BAGI ANAK USIA DINI DI PAUD PELITA PERUMNAS II WAENA, JAYAPURA - Kogoya, Wilius; Jamal, Ode; Krobo, Adrianus; Benggan, Willem (LPPM Uncen, 2024)
Early Childhood Education is the main foundation for strengthening character, including the character of mutual cooperation. Although the character has been known in children, but along with the progress of the era and triggered by the increasing busyness of parents, the character of mutual cooperation has faded and been replaced by a high individualistic attitude. There needs to be an effort to re-cultivate the character of mutual cooperation in children. The devotion to strengthening the character of mutual cooperation at PAUD Pelita aims to help early childhood in developing the character of mutual cooperation from an early age. Children are given practical experience in sharing, working together, and supporting each other in various daily activities at PAUD Pelita. It is hoped that these positive values and attitudes will continue to develop along with the growth and development of children when they continue their education to a higher level. This devotion is carried out using the lecture method, project method, and role-play method about the character values of mutual cooperation in Early Childhood. The results of the devotion show that children at PAUD Pelita are very enthusiastic and show a high interest in mutual cooperation. Of the 27 children at PAUD Pelita, 18 of them participated in cleaning the school room and yard by working together with enthusiasm. Meanwhile, 7 children only participated occasionally, and 2 other children were just spectators. This means that most children (66.67%) showed high enthusiasm in working together to clean the school room and yard, and 25.93% of children only participated occasionally. Meanwhile, a small number of children (7.41%) were just spectators. Likewise, with the project method using building blocks, 22 of them were involved, and only 5 children remained silent. These data show that the majority of children (81.48%) were actively involved in the project method using building blocks and only 18.52% of children were not involved. These data show that most children at PAUD Pelita actively participate both in cleaning the school environment and in the project method using building blocks. Thus, it can be concluded that the children of Pelita PAUD have quite strong roots in the character of mutual cooperation, but there is a lack of support from parents and the environment.